Health Promotion Behaviours and Level of Activities of Daily Living and Instrumental Activities of Daily Living Among Elderly People in West Region of Tehran: A Cross-Sectional Survey - Aghil Habibi Sola; Soghra Nikpoor; Mahboobe Rezaei; Hamid Haghani (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: As individuals live longer, health promotion behaviors get even more important, particularly with regard to maintaining functional independence and improving quality of life. The purpose of this study was to explore the relationship between health promotion behaviors and level of Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL) among elderly people in west region of Tehran. Methods & Materials: This was a descriptive-correlational study. A multi-stage sample of 410 community residents who were over 60 years old were selected from west region of Tehran. Participants who consented to participate in the study were interviewed with a structured questionnaire. The questionnaire consisted of 2-part; Health Promotion Behavior Checklist and questions related to status of physical functioning, which includes activities of daily living (ADLs) and instrumental activities of daily living (IADLs). Descriptive statistics and T-test were used to data analysis. Results: The results of the study showed that there were significant relations between ADLs and ' exercise or walking', 'drinking milk, eating dairy and meat', 'eating vegetables and fruits', 'low salt diet' and 'low fat diet' (P<0.05). Furthermore there were significant relations between the IADLs and 'smoking cessation', 'alcohol abstinence', 'exercise or walking', 'drinking milk, eating dairy and meat', 'eating vegetables and fruits', 'low salt diet' and 'low fat diet' (P<0.05). Conclusion: Study showed, health promotion behaviors and level of ADL and IADL are related meaningfully. Health care professionals should enhance the physical functioning in elderly people by facilitating health promotion behaviors through formal health promotion programs which focus on regular diet, exercise, and regular physical check-ups which will maintain and increase a healthy and active life.